Driving efficiency through innovation: exploring dynamic capabilities in Indian manufacturing small and medium scale enterprise - Mubarak Rahman P; Shakeb Akhtar; Shahbaz Babar Khan; Mohsin Khan; Manoharan M; Mohd Afjal (Cogent Business & Management)
Small and Medium Enterprises (SMEs) are pivotal to India’s manufacturing sector, significantly contributing to the national economy and job creation. This study distinctly explores the influence of innovation on manufacturing efficiency within SMEs, employing a stochastic frontier model (SFM) and Tobit regression analysis to scrutinize the effects of innovation inputs. Unlike prior studies, this work uniquely dissects the impact of various types of innovations—product, process, marketing, and organizational—on SME efficiency. Analyzing data from 380 SMEs, selected through stratified random sampling, this research uncovers that the average efficiency level of these enterprises exceeds 75%. This finding suggests the potential for a 25% increase in production using existing resources. The theoretical underpinnings of this study align more closely with the Resource-Based View (RBV), emphasizing the role of internal capabilities and resources in driving competitive advantage and sustainability. Practically, the findings advocate for nuanced policy initiatives that enhance innovation capabilities, thereby boosting the competitive stance of Indian manufacturing SMEs in less capital-intensive areas, crucial for job creation and rural industrialization. This deeper exploration of innovation types tailored to the SME sector offers significant implications for long-term strategic development.